Knowledge, use and failure of contraceptive methods among women from Marabá who have had abortions (Research, Society and Development, 2021)
Female contraception ranges from socioeconomic to political aspects. The United Nations considers access to safe and voluntary family planning to be a human right, as it is essential for promoting gender equality, advancing women's empowerment, and reducing poverty. In this context, the aim of this study was to analyze the knowledge, use and failure of contraceptive methods among women living in Marabá (PA), as well as the use of public health services. This is an observational and cross-sectional study, in which a questionnaire prepared by the researchers was applied in face-to-face interviews and using an electronic form. A total of 394 women living in the urban area of Marabá, literate and aged 18 years or over were included. The results showed that 21% (83) of the interviewees had already had an abortion and, of these, 8.43% had never been to the gynecologist/obstetrician, with the majority claiming to know and know how to use mainly the contraceptive pill, male condom and intramuscular injection, 29% did not use contraceptive methods at the time of the interview and 46% claimed to have already become pregnant using at least one method. The contraceptive pill, male condom and withdrawal were the ones that were most associated with failure in both groups. Thus, knowledge about the various options for contraceptive methods enables the most appropriate choice for women's sexual behavior and socioeconomic factors. The dissemination of theoretical-practical contents about the use of these resources offer better support for the rational and correct use of them, as well as the mitigation of failures.